2019
DOI: 10.1002/lary.27807
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Survival in Head and Neck Cancer: Impact of Site, Stage, Smoking, and Human Papillomavirus Status

Abstract: Objectives/Hypothesis Literature examining long-term survival in head and neck squamous cell carcinoma (HNSCC) with human papillomavirus (HPV) status is lacking. We compare 10-year overall survival (OS) rates for cases to population-based controls. Study Design Prospective cohort study. Methods Cases surviving 5 years postdiagnosis were identified from the Carolina Head and Neck Cancer Study. We examined 10-year survival by site, stage, p16, and treatment using Kaplan-Meier and Cox proportional hazard mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
162
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 31 publications
11
162
2
6
Order By: Relevance
“…In both OC and oropharyngeal cancer, we observed an increase in mortality risk for patients aged 460 years and those with stage III/IV SCC, which is similar to the findings reported by Ridder et al (15). Although a greater mortality risk was reported in men (15,21,23,24), this study did not find a survival difference between sexes.…”
Section: ' Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In both OC and oropharyngeal cancer, we observed an increase in mortality risk for patients aged 460 years and those with stage III/IV SCC, which is similar to the findings reported by Ridder et al (15). Although a greater mortality risk was reported in men (15,21,23,24), this study did not find a survival difference between sexes.…”
Section: ' Discussionsupporting
confidence: 91%
“…For locally advanced oropharyngeal cancer, chemotherapy combined with radiation treatment has been reported to significantly improve OS (33,34). Du et al (23) observed that 84% of oropharyngeal cancer patients had stage III-IV cancers, which is the same as the finding of this study (90%). Monteiro (35).…”
Section: ' Discussionsupporting
confidence: 84%
“…Sarcopenia and its effect on treatmentrelated complications and the clinical prognosis of HNC have recently attracted research attention. However, underestimation of the importance of sarcopenia continues to evolve when compared to the large number of studies that have been focused on different patient-and disease-related variables affecting the prognosis of patients with HNC (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 95% of HNC cases are head and neck squamous carcinoma (HNSC), commonly arising from the mucosa of oral cavity, oropharynx, hypopharynx, and larynx [2,3]. The epidemiology surveys showed that smoking and alcohol consumption, and human papillomavirus (HPV) infection are most common causative factors for HNSC [4][5][6]. Although there have been certain advances in HNSC treatment, in stage III and IV HNSC, 5-year survival rate is less than 50% [7].…”
Section: Introductionmentioning
confidence: 99%